HUBUNGAN PENGETAHUAN MENOPAUSE DENGAN KEMAMPUAN PEREMPUAN PRE-MENOPAUSE DALAM MENGATASI PERUBAHAN FISIK - Eva Yunitasari; Feni Elda Fitri; Sri Suharti; Nova Riana (Jurnal Ilmiah Keperawatan Indonesia (JIKI), 2026)
Menopause is a condition in which the menstrual cycle stops completely. The diagnosis of menopause is generally given to women between the ages of 45 to 55 after their periods have not appeared for about a year. When a woman does not experience menstrual bleeding for twelve consecutive months, this is known as natural menopause. This study aims to explore the relationship between menopause knowledge and pre- menopausal women's ability to cope with physical changes in Way Gelam Village. The methodology used in this study was a quantitative approach with a cross sectional research design with a sample size of 86 respondents. The population in this study consisted of mothers who were at climacterium age. The results of the study showed a p value of 0.0025 (0.05), which indicated a relationship between menopausal knowledge and the ability of pre-menopausal women in Way Gelam Village. This study is expected to provide insight to mothers who are at the age of climacterium, so that they can learn more about how to deal with the physical changes that occur during menopause.